THROUGH THE POSITIVE DISCIPLINE LENS: PRIMARY SCHOOL TEACHERS’ BUSY AGENDA - Tütüniş, Birsen; Yalman, Duygu (International Online Journal of Education and Teaching, 2023)
In primary school years, classroom management mostly occupies the agenda of teachers working at this level. In this context, the evaluation of educational environments from the perspective of the concepts of positive psychology has gained importance in recent years. The main aim of this study is to examine the discipline understanding of kindergarten, primary school and English teachers working at the primary education level in the lens of classroom management. Sequential explanatory design of mixed method research was used. Kindergarten, primary school, and English teachers (N=105) working in public schools in Istanbul, selected by random sampling, constitute the sample of the research. Teachers' thoughts on positive discipline were collected through a questionnaire. The findings obtained from the teachers' questionnaire responses led the researchers to conduct semi-structured interviews to obtain in-depth information about the subject. For this purpose, interviews were conducted with 9 teachers who were randomly selected from the sample group. According to the survey results, “disruption” in primary classes was on the top of the problems’ list teachers reported. In the semi-structured interviews, presenters asked the real cases in the teachers’ classes and disruption scenarios. Regardless of branch, stated that they faced similar problem behaviors in their classrooms.